2008
DOI: 10.1088/0953-2048/21/10/105020
|View full text |Cite
|
Sign up to set email alerts
|

Hollow carbon spheres as an efficient dopant for enhancing the critical current density of MgB2-based tapes

Abstract: Abstract:A significant enhancement of critical current density (J c ) and H irr in MgB 2 tapes has been achieved by the in situ powder-in-tube method utilizing hollow carbon spheres (HCS) as dopants. At 4.2 K, the transport J c for the 850 o C sintered samples reached 3.1×10 4 , and 1.4×10 4 A/cm 2 at 10 and 12 T, respectively, and were better than those of optimal nano-SiC doped tapes. The effects of different sintering temperature on lattice parameters, amount of carbon substitution, microstructure and J c o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Over the last 10 years, many research groups have made significant progress in improving the in-field J c of MgB 2 [9,10]. The addition of SiC [11][12][13], C [12,14], or B 4 C [15,16], doping with carbon nanotubes [17] or hollow carbon spheres [18], and increasing the sample packing density [19] are effective methods for improving J c . To date, it is confirmed that doping with carbon or carbon-based compounds is the best way to enhance the current-carrying capability of MgB 2 superconductor.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 10 years, many research groups have made significant progress in improving the in-field J c of MgB 2 [9,10]. The addition of SiC [11][12][13], C [12,14], or B 4 C [15,16], doping with carbon nanotubes [17] or hollow carbon spheres [18], and increasing the sample packing density [19] are effective methods for improving J c . To date, it is confirmed that doping with carbon or carbon-based compounds is the best way to enhance the current-carrying capability of MgB 2 superconductor.…”
Section: Introductionmentioning
confidence: 99%
“…When a compound with C is doped into , the C substitutes for B, thus introducing scattering that reduces electron mean free path and coherence length of the superconductor and hence increases the [19]. Simultaneously, the dopants effectively enhance pinning strength by introducing lattice distortion and new grain boundaries [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the strong links among MgB 2 grains, there is no much influence on its superconductivity when a sample was contaminated or doped by a small ratio. Experimental results reported by Wang's group (Wang et al, 2004) and Ma's group (Ma et al, 2006;Gao et al, 2008) showed that the critical current density and flux pinning in some doping were enhanced evidently. Several papers suggested also that there was no appreciable difference between a perfect MgB 2 sample and one with MgO or oxygen contamination, but the flux pinning was improved Przybylski et al, 2003;Zeng et al, 2001;Liao et al, 2003).…”
Section: Compound Superconductorsmentioning
confidence: 89%